Carbon, nitrogen, and water fluxes from turfgrass ecosystems - Lewis, Jason Douglas (Kansas State University, 2010)
Turfgrass covers 1.9% of the nation’s surface area and is the largest irrigated crop in the USA. Developed urbanized land is projected to double by 2025, which will increase turf’s environmental impact. Studies were conducted to evaluate environmental impacts by characterizing nitrogen, carbon, and water fluxes in turfgrass ecosystems. Emissions of nitrous oxide (N[subscript]2O), a major greenhouse gas and ozone depleter were measured from bermudagrass (Cynodon dactylon L. Pers. x C. transvaalensis Burtt-Davy) (bermuda), perennial ryegrass, (Lolium perenne L.) (rye), and zoysiagrass, (Zoysia japonica Steud.) (zoysia) under regional N management. In a separate study, N2O fluxes were measured from bermuda fertilized with controlled-release N fertilizers including polymer-coated and organic-N, and quick release urea. Emissions of N2O were measured using static surface chambers and gas chromatography. Zoysia, with less N requirements, had lower emissions than bermuda. Cumulative N[subscript]2O emissions were similar among N types. To measure water and carbon fluxes, a portable non-steady state chamber was designed and tested. The chamber had minimal affects to the canopy during field measurements: leak values averaged <1.5 micromol CO[subscript]2 m[superscript]-2 s[superscript]-1; average chamber pressure was 0.09 Pa ±0.01 Pa; temperature rise inside the chamber averaged 0.74C; and the chamber had 90% photosynthetically active radiation transmittance. Using the chamber, differences were detected in net photosynthesis (Pnet), gross photosynthesis (Pg), evapotranspiration (ET), canopy stomatal conductance (gc), and water use efficiency (WUE) in well-watered tall fescue (Festuca arundinacea Schreb.), Kentucky bluegrass (Poa pratensis L.) (KBG), zoysia, and bermuda. Irrigation requirements, visual quality ratings, and genetic rooting potential of 28 KBG cultivars and 2 Texas bluegrass hybrids (P. pratensis x P. arachnifera Torr.) were quantified in greenhouse and rainout facility studies. Average water applied ranged from 23.4 to 40.0 cm among cultivars. Bedazzled, Preakness, and Bartitia required less water and had higher average quality than other cultivars. Compact America and Mid-Atlantic phenotypes exhibited greatest potential for success in integrating reduced water inputs with maintenance of acceptable visual quality. Results indicated that turfgrass management could mitigate N[subscript]2O emissions and conserve water while maintaining healthy turfgrass, and the new chamber will enhance turfgrass studies by providing rapid measurements of photosynthesis.
Keywords: Turfgrass; Nitrous Oxide; Non-steady State Chamber; Photosynthesis; Kentucky bluegrass cultivars; Irrigation requirements; Agriculture, Agronomy (0285); Biology, Botany (0309)